Pregnancy in patients with multiple sclerosis. (12th August 2021) - Arneth, Borros M
Abstract : Multiple sclerosis (MS) is an autoimmune disorder that affects ~2.5 million people globally. Women of reproductive age are highly susceptible to this disease. This study aims to explore the association between MS and pregnancy. Articles related to the topic under investigation were identified; the search terms included "pregnancy", "multiple sclerosis", "MS", and "women". Only articles published between 2010 and 2020 were included in the review. This review shows that researchers have attempted to explore the link between pregnancy and MS, and the results from previous studies indicate that pregnancy reduces the risk of MS relapse. However, evidence suggesting that pregnancy can affect the long-term progression of MS is lacking. The research results also indicate that MS does not increase the risk of maternal and fetal complications. MS remains a serious autoimmune disorder that affects many women worldwide. The data gathered during this review indicate that a significant correlation exists between pregnancy and MS relapse rates. The findings presented in this review can aid in the management of MS during pregnancy. Furthermore, these research results provide vital insights that caregivers can use to monitor patients with MS during pregnancy.